Correlation Between Prognostic Nutritional Index and Heart Failure in Adults with Diabetes in the United States: Study Results from NHANES (1999–2016) - Qiyuan Bai; Hao Chen; Zhen Gao; Xuhua Li; Jiapeng Li; Shidong Liu; Bing Song; Cuntao Yu (Reviews in Cardiovascular Medicine)
Background: The relationship between diabetes and heart failure significantly impacts public health. This study assessed the prognostic nutritional index (PNI) as a predictor of heart failure risk in adult diabetic patients. Methods: An analysis was performed on 1823 diabetic adults using data collected from the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2016. Serum albumin levels and lymphocyte counts were combined to calculate the PNI. We used descriptive statistics categorized by PNI quartiles and performed multivariate logistic regression to adjust for variables including age, gender, ethnicity, and coexisting medical conditions. Results: The median age (mean ± SD) was 59.942 ± 12.171 years, and the mean value ± SD of the PNI was 52.412 ± 5.430. The prevalence of heart failure was 7.405%. In the fully adjusted model, for each 1-unit increase in PNI, the risk of heart failure decreased by 8.2% (odds ratio (OR), 0.918; 95% confidence interval (CI) 0.884, 0.953). Participants in the highest PNI quartile (Q4) had a 63% reduced risk of heart failure compared to those in the lowest quartile (Q1). Tests for interactions did not reveal any statistically significant differences among these stratified subgroups (p for interaction > 0.05). Conclusions: This study demonstrated that a higher PNI was significantly associated with a decreased prevalence of heart failure in adults with diabetes.